Neurogenic Contraction Induced by the Antiarrhythmic Compound, AVE 0118, in Rat Small Mesenteric Arteries. (3rd April 2014) - Kun, Attila; Seprényi, György; Varró, András; Papp, Julius Gy.; Pataricza, János
Abstract The purpose of this study was to investigate the vasoactivity of two inhibitors of potassium ion (K+) channels, a potential antiarrhythmic compound, AVE 0118, and 4‐aminopyridine (4‐AP). Basal and stimulated tones of rat small mesenteric arteries as well as the possible involvement of KV1.5 ion channel in the mechanism of vascular effect induced by the compounds were analysed. The standard organ bath technique for vascular tone and immunohistochemistry for the localization of ion channels in the arterial tissue were performed. Third‐ or fourth‐order branch of arterial segments was mounted in myographs for recording the isometric tension. AVE 0118 (10−5 M) and 4‐AP (10−5 M) modulated neither the basal tone nor the contraction induced by noradrenaline but increased the contraction evoked by electrical field stimulation, sensitive to the block of alpha‐1 adrenergic receptors. KV1.5 ion channel‐specific immunostaining demonstrated the presence of immunoreactive nerves, and Schwann‐cell‐specific (S100) immunostaining confirmed the presence of myelin sheath in rat small mesenteric arteries. The study supports an indirect, sympathetic effect of AVE 0118 similar to that of 4‐AP, which is mediated, at least in part, by blocking neuronal KV1.5 type potassium ion channels in the medio‐adventitial layer of rat small mesenteric artery.